If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.47 = log(x) Multiply glo * x 0.47 = glox Solving 0.47 = glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1glox' to each side of the equation. 0.47 + -1glox = glox + -1glox Combine like terms: glox + -1glox = 0 0.47 + -1glox = 0 Add '-0.47' to each side of the equation. 0.47 + -0.47 + -1glox = 0 + -0.47 Combine like terms: 0.47 + -0.47 = 0.00 0.00 + -1glox = 0 + -0.47 -1glox = 0 + -0.47 Combine like terms: 0 + -0.47 = -0.47 -1glox = -0.47 Divide each side by '-1lox'. g = 0.47l-1o-1x-1 Simplifying g = 0.47l-1o-1x-1
| 0.11x=56 | | 5-x=8-x-3 | | 4x-17=4x | | 16=4(1+7x)-8(3x-5) | | f=6/5(n-18) | | 8-3(2x+3)=11 | | 4x-5=4x+12 | | -3(2x+3)=11 | | g=5/3(p-49) | | 4-5-13-18+2= | | 14=8x+7-x | | 458000*9= | | ln(x-4)=6 | | 90=2(7x+3) | | 3x+5x-8+4-11+17x-42+7x=-6 | | -252=-7(-6x+6) | | -91=-7(3r+4) | | 8w-14=434 | | 3(-5x+2)=-84 | | 6x+27=36 | | 7x+9y=103 | | 2x^2+-2x^2= | | (5y+3)(1+y)=0 | | (x-3)-2=6-2(x-1) | | -126=-3(-6-8n) | | -18-3p=-(p+4) | | 9y^3-11x^2+2-13y^3-15x^2= | | 2b+3b-4b+3=17 | | 10y^3-11x^2+2-12y^3-13x^2= | | -82=-2(6-5r) | | 18y^2-18x^3+2-18y^4-18x^5= | | 5(3x+7)-11=54 |